2018
DOI: 10.1002/lary.27474
|View full text |Cite
|
Sign up to set email alerts
|

Sarcomatoid Carcinoma in the Parotid Gland: A Review of 30 Years of Experience

Abstract: 2b. Laryngoscope, 2018.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 24 publications
(57 reference statements)
1
8
0
Order By: Relevance
“…Accepted survival predictors include high tumour stage, neck lymph node metastasis, perineural invasion, lymphovascular invasion, pathological tumour grade, neutrophil-to-lymphocyte ratio, resection margin, and intraparotid node metastasis [1, 3, 2224]. Niu et al [23] retrospectively enrolled 35 patients with sarcomatoid carcinoma in the parotid gland, concluding that perineural invasion was the most important predictive factor. Chang et al [24] analysed the oncologic outcome in 98 patients with primary parotid cancer and found that the pathological T stage, resection margin, external parenchymal extension, pathological lymph node status, and maximum standardized uptake value were significantly related to DSS by univariate analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Accepted survival predictors include high tumour stage, neck lymph node metastasis, perineural invasion, lymphovascular invasion, pathological tumour grade, neutrophil-to-lymphocyte ratio, resection margin, and intraparotid node metastasis [1, 3, 2224]. Niu et al [23] retrospectively enrolled 35 patients with sarcomatoid carcinoma in the parotid gland, concluding that perineural invasion was the most important predictive factor. Chang et al [24] analysed the oncologic outcome in 98 patients with primary parotid cancer and found that the pathological T stage, resection margin, external parenchymal extension, pathological lymph node status, and maximum standardized uptake value were significantly related to DSS by univariate analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Sarcomatoid carcinoma in other sites of the head and neck, especially hypopharynx and parotid, has also been associated with a high rate of PNI. 26,27 Due to this strong association and poor outcomes thereafter, we need to consider intensification of adjuvant therapy in the presence of PNI.…”
Section: Discussionmentioning
confidence: 99%
“…Because GL tends to be confined to the gastric wall for prolonged periods before tumor spread, its prognosis is better than that of GAC ( 17 ). Previous literature has found that SC in the parotid gland, lung, hypopharynx, liver and pancreas have poor prognoses due to metastasis or recurrence, with a survival period of a few months ( 3 , 22 25 ). Similarly, GSC patients also died or developed metastasis or recurrence within a few months, or it was already in the advanced stage at the first diagnosis.…”
Section: Discussionmentioning
confidence: 99%